Variation in TAS2R receptor genes explains differential bitterness of two common antibiotics - Nolden, Alissa A.; Hayes, John E.; Feeney, Emma L. (Frontiers in Genetics, 2022)
For pharmaceuticals to deliver their full benefits with maximum efficacy, patients need to follow recommended dosing schedules, in terms of amount and frequency. Unfortunately, the aversive taste of many drugs, especially bitterness, can reduce patient compliance in oral liquid formulations. Given common genetic differences in bitter taste receptor genes (TAS2Rs), some individuals may be at increased risk for poor compliance due to heightened bitterness that becomes a barrier to proper use. Here we report on the sensory profile of two antibiotics, chloramphenicol and ofloxacin, investigating whether bitterness intensity associates with nominally functional TAS2R variants. Participants (n=143) rated suprathreshold intensity on a general Labeled Magnitude Scale (gLMS) for chloramphenicol and ofloxacin; propylthiouracil (PROP) was included as a control, given robust prior associations with TAS2R38 variants. The dominant sensation from chloramphenicol and ofloxacin was bitterness, falling just below ‘moderate’ on a gLMS. TAS2R38 diplotype associated with variable bitterness of chloramphenicol and PROP, but not ofloxacin. The bitterness of ofloxacin associated with a TAS2R9 SNP (V187A). This pilot study provides novel evidence on differences in the bitterness from two antibiotics, which are associated with TAS2R variants. Improved understanding of individualized barriers to patient compliance, especially for oral formulations, can guide future efforts to optimize delivery systems for improved compliance.